Mapping the educational metaverse: A bibliometric analysis of trends, influences and future directions - Clarice Wider; Walton Wider; Yoon Fah Lay; Muhammad Ashraf Fauzi; Jingjing Li; Jem Cloyd M. Tanucan (Emerald Publishing, 2025)
This study investigates the evolving role of metaverse technologies in education through bibliometric analysis. It aimed to identify trends, influential studies and emerging areas within the application of the metaverse in educational contexts. A systematic bibliometric analysis was conducted using the Web of Science (WoS) database. Citation, co-citation and co-word analyses were applied to identify key authors, institutions and thematic clusters in the literature on metaverse technologies in education. The results indicate a significant increase in research interest from 2020 to 2023, with China, the US and South Korea leading in output. Three main clusters emerged from the co-citation analysis: technological development, educational integration and the adoption of metaverse technologies. Co-word analysis revealed five thematic areas: immersive learning environments and advanced educational technologies. This study offers a systematic identification of current trends, research gaps and future directions for metaverse educational applications. It provides a valuable resource for educators, policymakers and researchers, emphasizing the need for further exploration of the long-term impact and ethical considerations of using immersive technologies in learning environments.